2021
DOI: 10.1007/s40122-021-00330-4
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin has Longer-Term Efficacy for the Treatment of Chronic Pelvic Pain in Women: A Systematic Review and Pilot Meta-analysis

Abstract: Introduction: Gabapentin has potential analgesic benefits in patients with neuropathic pain, such as post-herpetic neuralgia and diabetic peripheral neuropathy neuropathic pain. However, its efficacy in women with chronic pelvic pain (CPP) remains contradictory. In the present study, we performed a systematic review and meta-analysis of randomized controlled trials (RCTs) to ascertain the efficacy of this treatment. Methods: We systematically reviewed RCTs published in PubMed, Embase, the Cochrane Library, Web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
(108 reference statements)
1
5
0
Order By: Relevance
“…The results showed that neither including nor excluding the trial of Horne et al had a significant alteration for the primary outcomes (see Table 1 ). Besides, it is noteworthy that our results [ 1 ] are consistent with those from Lewis et al, 2016, which conducted by their team [ 3 ]. Similarly, Putzke and colleagues also found that gabapentin had a longer-term analgesic effect (3 years) for pain after traumatic spinal cord injury [ 4 ].…”
Section: Key Summary Pointssupporting
confidence: 93%
See 2 more Smart Citations
“…The results showed that neither including nor excluding the trial of Horne et al had a significant alteration for the primary outcomes (see Table 1 ). Besides, it is noteworthy that our results [ 1 ] are consistent with those from Lewis et al, 2016, which conducted by their team [ 3 ]. Similarly, Putzke and colleagues also found that gabapentin had a longer-term analgesic effect (3 years) for pain after traumatic spinal cord injury [ 4 ].…”
Section: Key Summary Pointssupporting
confidence: 93%
“…Thank you for informing us about the letter discussing the results of “Gabapentin has Longer-Term Efficacy for the Treatment of Chronic Pelvic Pain in Women: A Systematic Review and Pilot Meta-analysis” [ 1 ]. Meanwhile, we also appreciate the comments by Vincent et al about our research.…”
Section: Key Summary Pointsmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review that included four randomized controlled trials and 469 participants showed that the anticonvulsant gabapentin reduced CPP in women after six months of use, with the principal side effects being dizziness and somnolence. 145 In a Cochrane review that included 45 studies and 11,906 participants, pregabalin reduced pain by at least 30% in patients with diabetic and post-herpetic neuropathy at a dose of 300 mg/day and in patients with post-traumatic neuropathic pain, whether classified as mixed or not, at a dose of 600 mg/day, with similar side effects to those found with gabapentin. 146 Extrapolating these data, pregabalin could be recommended for the treatment of CPP.…”
Section: Pharmacological Treatmentmentioning
confidence: 92%
“…We were concerned to read the article entitled “Gabapentin has Longer-Term Efficacy for the Treatment of Chronic Pelvic Pain in Women: A Systematic Review and Pilot Meta-analysis”, published recently by Fan and colleagues [ 1 ], which concluded that gabapentin could be a potential treatment option for chronic pelvic pain in women. We believe that the methodology used in this systematic review is inappropriate, and thus draws erroneous conclusions with the potential to expose women with chronic pelvic pain to unnecessary risk.…”
Section: Key Summary Pointsmentioning
confidence: 99%